A Rain Garden for Nitrogen Removal from Storm Runoff in Tropical Cities - Fajardo-Herrera, Reinaldo J. (2019)
Rain gardens are recessed landforms covered with plants, strategically placed in cities to capture rainwater from runoff, thus avoiding the entry of contaminants and excessive nutrients into aquatic ecosystems. Despite their importance, the implementation of this type of technology in tropical coastal cities has been limited. A rain garden at scale was built at the facilities of the Universidad de Cartagena, Colombia, in order to determine the removal rates of nitrogen compounds (nitrites, nitrates, TKN, ammonia, and total nitrogen) from simulated storm runoff containing 25 mg of N/L of water. The results show that the proposed model of a rain garden is able to reduce the levels of nitrogen successfully when the rate of incoming runoff is not greater than 0.91 L/min/m2 and represents an alternative for the management of storm runoff with nitrogen compounds in tropical cities.